A Study on Geopolitical Risk of the Belt and Road Construction in Central Asia (International relations and international law Journal, 2022)
The Belt and Road Initiative is a cross-regional cooperation framework linking China and the three continents of Asia, Africa and Europe. The proposal of the "One Belt, One Road" construction conforms to the trend of the world and China's development, and expresses China's determination to deeply integrate into the world political and economic system. Central Asia is an important part of China's major neighboring diplomacy. The joint construction of the "Belt and Road" in Central Asia is an important decision for China to maximize the common interests with the Central Asian region on the basis of a profound grasp of the new international political and economic situation and new trends. The independence of Central Asian countries is relatively short. Under the influence of many international and domestic factors, the geopolitical risks and challenges in the region are relatively severe, which will bring difficulties and obstacles to the advancement of the “Belt and Road” initiative in Central Asia. Therefore, it is of great research value and theoretical significance to effectively predict and control the geopolitical risks of the Belt and Road construction in Central Asia.This paper analyzes the background and reasons of taking Central Asia as the research area, and comprehensively analyzes the geopolitical significance of Central Asia to the construction of the “Belt and Road”, including from an objective point of view, the geopolitics of the “Belt and Road” in Central Asia benefits, and the consensus of Central Asian countries on the construction of the “Belt and Road” on the subjective level. This paper systematically analyzes the geopolitical risks and their factors in Central Asia under the construction of the “Belt and Road”, mainly from four aspects: bilateral, major power game, multilateral relations, and regional security. influencing factors. It provides ideas for avoiding the geopolitical risks faced in the implementation of the "Belt and Road" construction in Central Asia.Key words: “Belt and Road”; China; Central Asia; geopolitics; risk